Logico-analytical expertise of texts with a description of procedures based on intelligent technologies - Hutsa, Oleh; Dvukhhlavov, Dmytro Eduardovych (Novij Svit-2000, 2025)
Analysis of existing approaches to the development of procedures in a textual form containing description of branching processes (in particular in legal texts) was made. It was established that visualization with the help of the system analysis methods (in particular, logical schemes made in BPMN notation) is the most effective tool for developing branching processes. It was also established that the absence of clear rules for development of Procedures in a textual form causes a fairly large number of errors in descriptions of the branching processes worked out by the specialists having no sufficient skills in using algorithmizing. The Intelligent Technology was developed for checking textual Procedures containing descriptions of branching processes. It is based on visualization using BPMN notation which allows one to find errors of logical coherence and completeness. Effectiveness of the proposed Intelligent Technology was demonstrated on the examples of checking legal texts with a description of branching processes of legislation of a number of countries of the world. The developed Intelligent Technology is quite simple in its mastering for the specialists possessing a certain level of skills in algorithmization and can be applied in any sphere of activity describing processes in a textual form.
Keywords: branching processes; BPMN notation; logical errors in legal texts; textual description of processes; visualization of process description